Application of hybrid electrocoagulation–filtration methods in the pretreatment of marine aquaculture wastewater - Jianping Xu (IWA Publishing, 2021)
The aim of this study was to provide technical means and data support for enhancing the filtration pretreatment capacity of a recirculating aquaculture system. A continuous flow electrocoagulation (EC)–filtration system was designed and its application in the pretreatment of marine aquaculture wastewater was studied. The influences of anode combination modes, hydraulic retention times (HRTs) of the EC reactor and filter pore sizes on the water treatment capacity were investigated. Results showed that EC could significantly enhance the treatment efficiency of the filtration equipment used in subsequent steps. Al-Fe electrodes used as anode led to better processing capacity of this system, and the optimum anode was 3Al + Fe. With the increase of HRT and decrease of filter pore size, the enhanced effect of the EC process on the filter was more obvious. When the current density was 19.22 A/m2, the anode was 3Al + Fe, the HRT was 4.5 min and the filter pore size was 45 μm, the removal efficiency of the system for Vibrio, chemical oxygen demand, total ammonia nitrogen, nitrite nitrogen (NO2−-N), nitrate nitrogen (NO3−-N) and total nitrogen was 69.55 ± 0.93%, 48.99 ± 1.42%, 57.06 ± 1.28%, 34.09 ± 2.27%, 18.47 ± 1.88% and 55.26 ± 1.42%, respectively, and the energy consumption was (26.25 ± 4.95) × 10−3kWh/m3. HIGHLIGHTS The combination technology of EC and filtration was used for the pretreatment of aquaculture wastewater.; The filtration capacity of physical filtration equipment was improved through the EC–flocculation.; Al-Fe combined anode was used to improve the treatment capacity of the EC–filtration system.;